2004
DOI: 10.1089/gte.2004.8.133
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Two Novel BRCA1 Germ-Line Mutations Involving Splice Donor Sites

Abstract: Deleterious BRCA1 mutations have significant clinical implications for the patients that carry them. Point mutations in critical functional domains and frameshift mutations that lead to early termination of protein translation are associated with a 60-80% risk of breast cancer and a 20-40% risk of ovarian cancer. In contrast, the significance of mutations located in intronic regions of BRCA1, even in the setting of a family history of breast and ovarian cancer, is not always clear. Some of these mutations occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
0
10
0
3
Order By: Relevance
“…For an initial pilot to assess feasibility of review, splicing assay data for 21 BRCA1 (NM_007294.3) or BRCA2 (NM_000059.3) sequence variants (22 assays) were drawn from four studies (Table ), published by four different groups across a period of 7 years [Brose et al., ; Claes et al., ; Farrugia et al., ; Walker et al., ]. These data were then comprehensively assessed by basic and clinical researchers from up to nine different ENIGMA study sites from around the world.…”
Section: Methodsmentioning
confidence: 99%
“…For an initial pilot to assess feasibility of review, splicing assay data for 21 BRCA1 (NM_007294.3) or BRCA2 (NM_000059.3) sequence variants (22 assays) were drawn from four studies (Table ), published by four different groups across a period of 7 years [Brose et al., ; Claes et al., ; Farrugia et al., ; Walker et al., ]. These data were then comprehensively assessed by basic and clinical researchers from up to nine different ENIGMA study sites from around the world.…”
Section: Methodsmentioning
confidence: 99%
“…12 Consistently, germline mutations in BRCA1 exon 11 promote the expression of BRCA1Δ11b. 13 Additional germline mutations in BRCA1 have also been identified, causing aberrant splicing 14,15 or altering alternative splicing. [16][17][18] Since a single pre-mRNA can be processed to generate multiple functional isoforms, it is essential to analyze the interrelationship between wildtype and splice variants when characterizing gene functions in cancer or disease.…”
Section: Introductionmentioning
confidence: 99%
“…These variants include missense variants leading to amino acid changes, variants located in intronic regions and silent mutations [8][9][10][11][12]; they are usually referred to as VUS and pose a real problem in genetic counseling. An increasing number of recent studies have demonstrated the effect of several variants on the correct splicing of the BRCA1 and BRCA2 genes [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%